The West Bank of Greater New Orleans : A Historical Geography - Campanella, Richard (Book collections on Project MUSE., 2020)
"The West Bank has been a vital part of greater New Orleans since the city's inception. It has been the Kansas, the Birmingham, the Norfolk, Atlanta, Pullman, and Fort Worth of the metropolis that is, its breadbasket, foundry, shipbuilder, railroad terminal, train manufacturer, and livestock hub. It had been the Gulf South's St. Louis, in that it had a diversified industrial sector as well as a riverfront, mercantilist, and agricultural economy. It served as a jumping off point to the Western frontier, and a Cannery Row for the estuarine abundance to the south. The West Bank has also been the Queens and Oakland of New Orleans an affordable, if rather plain, border district, proud but not pretentious, pleasant if not prominent, comfortable with its place even though at time anxious about the grandiloquence of its cross river counterpart. The West Bank is home to some of the most diverse demographics in the region, including many immigrants. It is also home to some of the most locally rooted populations, folks who speak in local accents, who retain old cultural traits with a minimum of pomp and self awareness, and, in some cases, who maintain family ownership of lands held since antebellum times. Richard Campanella is the first to examine the West Bank holistically; most books about New Orleans treat it as a sideshow or an afterthought, if at all. The limited literature specifically about the West Bank has been at the community or jurisdictional level; there are books and monographs, for example, on Algiers, Gretna, and Westwego, and Jefferson Parish as a whole. Various dissertations and government reports have been published on specific West Bank topics and spaces therein. However, Campanella's work is the only comprehensive analysis of the whole sub-region. He positions the West Bank of greater New Orleans front and center, viewing it as a legitimate sub region unto itself, with more holding it together than dividing it into parts. Campanella understands West Bankers to have had agency in their own place making, and he challenges the notion that their story is subsidiary to a more important narrative across the river. The West Bank is not a traditional history of mayoral administrations and important political figures such as Martin Behrman and John Alario. Nor is it a cultural history, paying homage to beloved natives such as Mel Ott and Frankie Ford. Rather, it is a historical geography that is, a spatial explanation of how the West Bank's cityscape came to be: its terrain, environment, land use, jurisdictions, waterways, industries, infrastructure, systems, subdivisions, neighborhoods, and settlement patterns, past and present. Put simply, Campanella's study explains how the map of the West Bank took shape, and it positions the sub region in a broader context by recognizing that many other metropolises have their "West Banks."--